Captured [large type] : from the frontier diary of infant Danny Duly - Lalire, Gregory (Wheeler Publishing, a part of Gale, Cengage Learning, 2014)
Even before his birth, Danny Duly relates his life story as his mother leaves his father in a Chicago asylum in 1866 and heads for her sister's home in the boomtown of Virginia City, encountering many colorful characters and giving birth to Danny along the way.